On the Efficacy of Silverberry (Elaeagnus pyriformis) for the Management of Oxidative Stress-Induced Male Infertility: an ex vivo Study (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Male infertility is a multifaceted medical condition that has a detrimental effect on reproductive health worldwide. Testicular dysfunction is mainly associated with oxidative damage caused by an unhealthy contemporary lifestyle. The present work utilized an ex vivo experimental model to examine the protective effect of resveratrol, derived from Elaeagnus pyriformis (EP) fruit, against H2O2-mediated oxidative testicular damage in rat. The pharmacological potential of EP fruit extract was evaluated using FTIR, GC-MS, and HR-Orbitrap LC-MS analyses to identify polyphenolic compounds. Resveratrol, a key polyphenol, was tested ex vivo at varying concentrations of 5 – 40 mg/L to assess its effects on antioxidant enzyme activity, lipid profile (TC, HDL-C, TG, LDL-C), and rat sperm viability under oxidative stress, employing acridine orange-propidium iodide dual staining. The results are corroborated by an in-silico molecular docking analysis, which revealed significant inhibitory potential of resveratrol (-7.8 kcal/mol) against the stress protein NOX2. Resveratrol treatment found to restore altered lipid metabolism, reduce NADPH oxidase (NOX) activity by 39–55%, upregulation of key enzymatic [superoxide dismutase (SOD; ~165–172%), catalase (CAT; ~16–38%)] and non-enzymatic antioxidants [glutathione (GSH; ~18.5–91.43%)], regenerate histological structures, and maintains sperm viability in an ex vivo model. This study investigated the protective effects of resveratrol, found in Elaeagnus pyriformis, against oxidative damage in the testes. The findings indicate the potential of EP to be an effective remedy for male infertility problems caused by stress.
Keywords: unhealthy diet; oxidative stress; underutilized fruit; bioactive compound; resveratrol; sperm viability